Burden of Neurodegenerative Diseases in a Cohort of Medical Examiner Subjects - Uryu, Kunihiro; Haddix, Terri; Robinson, John; Nakashima-Yasuda, Hanae; Lee, Virginia M.-Y.; Trojanowski, John Q. (Journal of forensic sciences, 2010)
:  Here we report studies of the burden of neurodegenerative neuropathologies in a cohort of Medical Examiner (ME) subjects from the County of Santa Clara (California) to determine if this unique population of decedents manifested evidence of neurodegeneration that might underlie causes of death seen in an ME practice. We found that 13% of the brains from ME cases showed significant tau pathology, including 55% of those 65 years old and older and 63% of those 70 years old and older. The histochemical and immunohistochemical findings were consistent with Alzheimer’s disease (AD) in 7 subjects and frontotemporal lobar degeneration (FTLD) tauopathy type in six cases. There were no cases of Parkinson’s disease, dementia with Lewy Bodies or other neurodegenerative conditions. Our study suggests that decedents >65 years of age in an ME practice are afflicted by common causes of dementia such as AD and FTLD which could contribute wholly or in part to their causes of death.